Well-being and fair distribution : beyond cost-benefit analysis - Adler, Matthew D. (New York ; Oxford : Oxford University Press, 2011)
A comprehensive philosophically grounded argument for the use of social welfare functions as a framework for governmental policy analysis.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Welfare economics; Public welfare; Well-being.; Distributive justice